Good Corporate Governance Principles act as Mediators of The Influence of Organizational Commitment, Leadership, and Organizational Culture on Employee Performance - Syahnur, Ogi F.; Elmi, Farida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aimed to determine the influence of good corporate governance principles as an intervening variable on organizational commitment, leadership, and organizational culture on employee performance.Methodology/approach – The population includes all employees of one of Pertamina's subsidiaries, namely PT Pertamina Training and Consulting, located at DKI Jakarta. Probabilistic sampling technique with simple random sampling was used, obtaining a sample of 162 employees. The method of data analysis used is the partial least squares structural equation (SEM-PLS).Findings – The research results show that the variables of organizational commitment, leadership and organizational culture have a positive and significant impact on employee performance and on good corporate governance principles. In addition, good corporate governance principles partially mitigated the significant positive effects of organizational commitment, leadership, and organizational culture on employee performance.Novelty/value – Companies should increase employee commitment to the business by focusing on employee results, enhancing professionalism in corporate governance and implementing employee promotion programs. The relationships in the concepts of this study and potential avenues for further development in future research may involve exploring associations with employee performance and looking at variables related to behavior, attitudes, or other factors that affect employee performance.